Building academic staff capacity for using esimulations in professional education for experience transfer : a guide to designing, developing, using and evaluating esimulations for professional learning in Australian higher education. - Cybulski, Jacob; Holt, Dale; Segrave, Stephen; O'Brien, David; Munro, Judy; Corbitt, Brian; Smith, Ross; Dick, Martin; Searle, Ian; Zadeh, Hossein; Sarkar, Pradipta; Keppell, Mike; et al. (Australian Learning and Teaching Council, 2010)
Resource produced from a project that aimed to transfer knowledge and build organisational capacity to develop, deliver and evaluate digital simulations (eSimulations) to enhance professional learning in the Australian higher education sector. Knowledge was initially transferred from the lead institution, Deakin University, to the partner universities, RMIT University and Charles Sturt University (CSU), to achieve this aim. The project revealed both the potential and limits of knowledge transfer to build organisational capacity in the partner institutions. Over time knowledge was in turn transferred from the partner universities to the lead institution. The project's action research and action learning approach led to the creation of the eSimulations Organisational Capacity Building Framework. This is a guide to designing, developing, using and evaluating esimulations for professional learning in Australian higher education.